Joseph Smith : History, Methods, and Memory - Barney, Ronald O., 1949- (Book collections on Project MUSE., 2020)
"Joseph Smith studies have long been shaped by the polemical atmosphere that surrounds Smith's claims of and to divine authorship. Even after a half-century of serious scholarship, fundamental questions remain about how to best interpret features of Smith's life and writing. Smith's own "History of Joseph Smith" (edited and revised at the beginning of the twentieth century by B. H. Roberts) created an enduring image of the man and influenced Mormon theology, doctrine, and polity for generations. With new historical documents now available, a reappraisal of Smith and Mormon beginnings warrants attention. Ronald O. Barney a former editor of the Joseph Smith Papers applies new interpretations to Joseph Smith in history and memory as he re-examinesSmith's surviving writings and what Smith's contemporaries wrote about him. The book explores the best methodologies for appraising the historical record, a review of Smith's worldand its contextual background, an analysis of his foundational experiences, and a characterization of Smith as a man and prophet. Though the premise of re-evaluation may be unsettling to traditionalists, a modern reconsideration of the historical record's entire range of sources is necessary to fashion a strategy for evaluating Smith and his enduring but complex legacy"--